PENYIDIKANTERHADAP TINDAK PIDANA PENGGUNAAN SPEKTRUM FREKUENSI RADIO TANPA IZIN STASIUN RADIO (ISR) OLEH RADIO PENYIARAAN SWASTA (PENELTIIAN DI BALAI MONITOR SPEKTRUM FREKUENSI RADIO KELAS II PEKANBARU) - Roni Gunawan Rajagukguk; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Private radio stations that do not have radio station licenses in recent years have had wide-ranging impacts in various sectors of life. The most affected sectors are the telecommunications sector which resulted in overlapping of frequency channels. Private radio broadcasting is closely related to radio frequency spectrum and satellite orbit, Article 33 Paragraph (1) of Law Number 36 Year 1999 concerning Telecommunication states. In accordance with the description above, the authors are interested to conduct research with the title of investigation of criminal acts of radio frequency spectrum use without radio station permit (ISR) by private broadcasting radio (research in radio frequency spectrum monitor Hall class II Pekanbaru). Then to find out the obstacles faced in the investigation of private radio broadcasting that does not have a radio station license. The last objective is to know the efforts made to overcome obstacles in the process of investigation of private radio broadcasting that does not have a radio station license. In writing this skirpsi, the author uses an approach that is empirical or sociological law research. While the data collection technique is the interview And the study of data using deductive method that is analyzing the problems of a general nature then drawn to conclusions in particular based on existing theories.